Megaloappendix: A Case Report - Abdel Hady A. Samaha; Ayman S. Tawfik; Tariq O. Abbas; Ashraf Abdelhamid (Case Reports in Surgery)
The vermiform appendix is an organ that can have variable sizes, locations as well as functional potentials. We describe here the longest and largest appendix removed measuring about 55 cm in length.